2015
DOI: 10.1016/j.amjmed.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Statin Therapy in Chronic Kidney Disease and Acute Myocardial Infarction: A Retrospective Cohort Study

Abstract: Background Whether there is a kidney function threshold to statin effectiveness in patients with acute myocardial infarction is poorly understood. Our study sought to help fill this gap in clinical knowledge. Methods We undertook a new-user cohort study of the effectiveness of statin therapy by level of estimated glomerular filtration rate (eGFR) in adults who were hospitalized for myocardial infarction (MI) between 2000 and 2008. Data came from the Cardiovascular Research Network. The primary clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Smith et al 30 reported an all-cause death rate of 119.3 per 1000 person-years in MI patients that initiated statins, based on data from the Cardiovascular Research Network. Two studies focused on stroke cohorts.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al 30 reported an all-cause death rate of 119.3 per 1000 person-years in MI patients that initiated statins, based on data from the Cardiovascular Research Network. Two studies focused on stroke cohorts.…”
Section: Mortalitymentioning
confidence: 99%
“…Incidence of CV-related mortality was reported in four studies, ranging from 1.0 to 94.5 (median: 21.1) per 1000 personyears 22,23,27,28 . Incidence of all-cause mortality was reported in eight studies, ranging from 9.7 to 486 (median: 52.6) per 1000 person-years [19][20][21][22][26][27][28][29][30] . Three studies included ASCVD patients.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest an article written by Smith et al 1 The authors performed a comparative effectiveness analysis of statin therapy by different levels of the estimated glomerular filtration rate (eGFR). They found relatively similar reduction in deaths and cardiovascular disease hospitalization across the range of eGFR, with higher rates in patients with lower eGFR.…”
Section: To the Editormentioning
confidence: 99%
“…У пациентов после ИМ статины сохраняли эффективность при дисфункции почек, за исключением 5 стадии ХБП [78][79][80]. Расчеты показывают, что для предупреждения одной смерти в течение 2 лет принимать статины необходимо 15 пациентам с ИМ с рСКФ <30 мл/мин/1,73 м 2 , а при рСКФ >90 мл/мин/1,73 м 2уже 67 пациентам [81].…”
Section: другие препаратыunclassified